2021
DOI: 10.1038/s41386-021-01055-w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of baclofen in a U.S. community population with alcohol use disorder: a dose-response, randomized, controlled trial

Abstract: Identification of new medications for alcohol use disorder (AUD) is important for improving treatment options. Baclofen, a GABAB agonist, has been identified as a potential pharmacotherapy for AUD. In a 16-week double-blind, randomized, placebo-controlled trial, we investigated 30 and 90 mg/day of baclofen compared to placebo and examined effects of dose, sex, and level of pretreatment drinking. One hundred and twenty participants with DSM-IV alcohol dependence (age 46.1 (sd = 10.1) years, 51.7% male) were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 40 publications
4
44
2
1
Order By: Relevance
“…These findings are consistent with a recently completed trial by Garbutt et al ( 22 ), which indicated the potential of an enhanced treatment effect for women compared to men. These authors found that women demonstrated a greater reduction in heavy drinking days and abstinence from alcohol ( 22 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are consistent with a recently completed trial by Garbutt et al ( 22 ), which indicated the potential of an enhanced treatment effect for women compared to men. These authors found that women demonstrated a greater reduction in heavy drinking days and abstinence from alcohol ( 22 ).…”
Section: Discussionsupporting
confidence: 92%
“…Baclofen, a selective g-aminobutyric acid type B (GABAB) receptor agonist, provides a potential treatment for alcohol dependence, with several clinical trials ( 19 22 ), and meta-analyses ( 23 , 24 ) demonstrating efficacy. We have previously reported that baclofen delays time to lapse and relapse relative to placebo ( 25 ) in addition to attenuating alcohol cue-elicited brain activation ( 26 ), cardiovascular response ( 27 ), and emotional regulation during high threat stimuli ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The last RCT tested 10 mg tid and 30 mg tid of baclofen with respect to placebo. Gender and level of pre-randomization drinking on response to baclofen were evaluated as moderators for efficacy or tolerability (107). A significant effect of baclofen in reducing heavy drinking days and increasing abstinent days was found.…”
Section: Accepted Manuscriptmentioning
confidence: 99%